2021
DOI: 10.3389/fmicb.2021.662461
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Potential Salmonella Phages Targeting Multidrug-Resistant and Major Serovars of Salmonella Derived From Broiler Production Chain in Thailand

Abstract: Salmonella is a major foodborne pathogen that causes foodborne disease in humans through consumption of contaminated foods, especially those of animal origin. Multiple Salmonella strains are antibiotic-resistant due to the common use of antibiotics in farm animals, including broiler farms. In this study, an alternative strategy using phage-based treatment was evaluated against Salmonella isolated from the broiler production. The prevalence of Salmonella spp. showed up to 46.2 and 44.4% in bedding samples from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 43 publications
1
35
0
Order By: Relevance
“…Antimicrobial resistance in Salmonella is increasing, likely due to the abuse/misuse of antibiotics in farmed animals, including pigs. AMR compromises the efficacy of antibiotics used to treat human infections, thus suggesting a reducing in antibiotic use in livestock (Pelyuntha et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial resistance in Salmonella is increasing, likely due to the abuse/misuse of antibiotics in farmed animals, including pigs. AMR compromises the efficacy of antibiotics used to treat human infections, thus suggesting a reducing in antibiotic use in livestock (Pelyuntha et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, scientists reported the isolation of diverse phages in SEA from different sample types, with potential activities against human pathogens (Table 2). Among the phages discovered in the region with notable activity against MDR organisms are: (1) phages vB_AbaM_PhT2 (Styles et al, 2020) and AB1801 (Wintachai et al, 2019), which exhibited anti-MDR A. baumannii activity, in vitro and in vivo, respectively, (2) phage UPM2146 (Assafiri et al, 2021), which exhibited activity against carbapenem-resistant K. pneumoniae, in vitro and in vivo, (3) phage C34 (Guang- Han et al, 2016), which controlled naturally resistant Burkholderia pseudomallei bacterial load, in vivo, (4) phage ΦHN10 (Phothichaisri et al, 2018), which exhibited the highest breadth of activity against various Clostridiodes difficile strains, in vitro, (5) phage ΦKAZ14 (Ahmad et al, 2015), which induced lysis of extended-spectrum betalactamase (ESBL)-producing Escherichia coli, in vitro, (6) phages UPMK_1 and 2 (Dakheel et al, 2019) and ΦNUSA-1 and 10 (Tan et al, 2020), which all exhibited lytic activity against methicillin-resistant Staphylococcus aureus (MRSA), and antibiofilm activity for the first two phages in in vitro experiments, (7) cocktail of phages vB_SenS_WP109, WP110, and WP128 (Pelyuntha et al, 2021), which induced lysis of multiple MDR Salmonella serovars, in vitro, and (8) phages KP1, 2 Poultry and farm feces, urban catchment, tissue samples Indonesia, Malaysia, Singapore Lau et al, 2012;Gan et al, 2013;Rezaeinejad et al, 2014;Ahmad et al, 2015;Vergara et al, 2015;Sellvam et al, 2018;Lukman et al, 2020;Dewanggana et al, 2021;Sjahriani et al, 2021;Waturangi et al…”
Section: Phages In Seamentioning
confidence: 99%
“…Dairy farm, poultry, clinical samples Malaysia, Thailand Wong et al, 2014;Wongsuntornpoj et al, 2014;Phothaworn et al, 2019Phothaworn et al, , 2020Pelyuntha et al, 2021 Shigella Staphylococcus phages (UPMK_1, UPMK_2, ΦNUSA-1, ΦNUSA-10)…”
Section: Salmonella Entericamentioning
confidence: 99%
See 1 more Smart Citation
“…These phenomena highlight the possibility of using phages to treat A. baumannii-associated SSTIs. In Thailand, a few studies on phage isolations have been reported, and there are no commercial phage products available nowadays [33][34][35]. Due to the emergence of MDR bacteria in Thailand similar to other countries worldwide, alternative strategies to control MDR bacterial infections, including phage and the combination of phages with other antibiotics, are attractive to investigate among researchers.…”
Section: Introductionmentioning
confidence: 99%